(untitled) (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2023)
The Pakchong-1 hybrid cultivar is a highly productive forage grass cross between elephant grass and pearl millet grass (Pennisetum purpureum x Pennisetum glaucum). The research objective was to determine the growth and production response of Pakchong-1 elephant grass to different fertilizer doses and cutting ages. The study was conducted at the JASTRU (Jonggol Animal Science Teaching and Research Unit) of IPB University. This study used a 3 x 3 factorial completely randomized design (3 doses of nitrogen fertilizer x 3 cutting ages) with 4 replications. The data was analysed using ANOVA and the Duncan Multiple Range Test. The fertilizer doses used were 100, 200, and 300 kg ha-1, and the cutting ages were 50, 60, and 70 days. The research results showed that the cutting age significantly increased plant height (180.53 – 210.90 cm), dry leaf weight (3.90 – 5.63 tons ha-1), dry stem weight (2.32 – 4.38 tons ha-1), and total dry weight (6.22 – 10.02 tons ha-1). However, biomass production was not affected. There was an interaction between the fertilizer dose and cutting age in terms of the number of tillers (1.99 – 5.15 tillers per clump) and the number of leaves (5.55 – 11.18 leaves per plant). Based on the research, the optimal point for obtaining the best results in terms of plant height growth, number of leaves, number of tillers, production of fresh biomass, dry weight of stems, dry weight of leaves, and total dry weight of Pakchong-1 elephant grass was a cutting edge of 60 days and the addition of 100 kg ha-1 of fertilizer. Key words: cutting age, fertilizer dosage, forage production, growth of pakchong